Liver stiffness is directly influenced by central venous pressure - Millonig, Gunda; Friedrich, Stefanie Sofia Anna; Adolf, Stefanie; Fonouni, Hamidreza; Golriz, Mohammad; Mehrabi, Arianeb; Stiefel, Peter; Pöschl, Gudrun; Büchler, Markus W.; Seitz, Helmut K.; Mueller, Sebastian (Journal of hepatology, 2010)
Background & Aims - Liver stiffness (LS) as measured by transient elastography [Fibroscan] offers a novel non-invasive approach to assess liver cirrhosis. Since Fibroscan seems to be unreliable in patients with congestive heart failure, it remains to be determined whether hemodynamic changes affect LS irrespective of fibrosis. - Methods & results - Using landrace pigs, we studied the direct relationship between the central venous pressure and LS measured by Fibroscan. Clamping of the inferior caval vein increased LS from 3.1 to 27.8kPa while reopening reversed LS within 5min to almost normal values of 5.1kPa. We then studied LS as a function of venous pressure in the isolated pig liver by clamping the upper and lower caval, portal vein and hepatic artery. The stepwise increase of intravenous pressure to 36cm of water column (3.5kPa) linearly and reversibly increased LS to the upper detection limit of 75kPa. We finally measured LS in 10 patients with decompensated congestive heart failure before and after recompensation. Initial LS was elevated in all patients, in 8 of them to a degree that suggested liver cirrhosis (median 40.7kPa). Upon recompensation with a median weight loss of 3.0kg, LS decreased in all 10 patients down to a median LS of 17.8kPa. Inflammation could not account for increased LS since initial liver enzyme counts were only slightly elevated and did not change significantly. - Conclusion - LS is a direct function of central venous pressure which should be considered when assessing the degree of fibrosis.
Erstmals am 3. Dezember 2009 online veröffentlicht
Gesehen am 26.04.2023